Amino Acids Content in Different Korean Cultivars of Rapeseed (Brassica napus) - Kim, Jae Kwang; Bong, Sun Ju; Park, Sang Un (Asian Journal of Chemistry, 2017)
This study assessed the variation in amino acid contents of five different Korean cultivars of rapeseed (Brassica napus). Twenty-two amino acids were detected in the cultivars of rapeseed and the amino acid content varied greatly among the cultivars. The Tamra cultivar contains the highest total quantity of amino acids, with values 43.29, 24.12, 6.46 and 3.43 % higher than the total amino acid contents of the Hanlla, Youngsan, Naehan and Tammi cultivars, respectively. The Tamra cultivar also contained the highest levels of eight different amino acids. The g-amino butyric acid content was very high in the cultivars and was higher than the levels of half of the other amino acids. The levels of alanine and arginine were also higher than those of the other amino acids irrespective of cultivar. The Tammi cultivar contains the highest levels of alanine and arginine, which were 2.03 and 5.59 times higher, respectively, than those in the Hanlla cultivar, which had the lowest concentrations of these amino acids. Moderate levels of the amino acids serine, glutamine, threonine, cysteine, valine, norvaline, phenylalanine and isoleucine were found in each cultivar, at quantities more than 10 mg/100 g dry weight. The levels of serine, cysteine, valine and phenylalanine in the Tamra cultivar were 1.65, 1.78, 2.52 and 3.25 times higher, respectively, than those in the Hanlla cultivar, which had the lowest concentrations of these amino acids. The levels of glutamate, vitamin U, histidine, tyrosine, methionine, tryptophan and leucine were the lowest of the amino acids measured irrespective of cultivar, with Tamra containing the highest levels for most of these amino acids. In conclusion, the present results demonstrate that Korean rapeseed cultivars contain variable quantities of amino acids, with the Tamra cultivar showing the greatest potential to serve as a commercial source of amino acids.